CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

For all non - negative integers x and y, f(x,y) is defined as below.
f(0, y) = y + 1
f(x + 1, 0) = f(x, 1)
f(x + 1, y + 1) = f(x, f(x + 1, y)) find f(1, 2)?


A
2
loader
B
4
loader
C
3
loader
D
Cannot be determined
loader

Solution

The correct option is B 4
f(1, 2) = f(0, f(1, 1));
Now f(1, 1) = f[0, f(1, 0)] = f[0, f(0, 1)] = f[0, 2] = 3
Hence, f(1, 2) = f(0, 3) = 4

Quantitative Aptitude

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image